Respiratory Syncytial Virus in Transplant: Stopping the Short-Term Spread, Solving the Longer-Term Problems - Wright, A. J.; Mah, A. (Emerging Transplant Infections, 2021)
Respiratory syncytial virus (RSV) causes signiﬁcant morbidity and mortality in immunocompromised hosts with particular burden among allogeneic hematopoietic stem cell transplant and lung transplant recipients. Affected patients have a substantial risk of secondary infection, ICU admission, or death. Improved diagnostic testing with better sensitivity has given new insights into the epidemiology of disease. In particular, it has highlighted the issue of nosocomial transmission and hospital outbreaks. These can be challenging to manage. Currently, treatment options include ribavirin and immunoglobulin replacement.

Clinical Manifestations and Management of Left Ventricular Assist Device-Associated Infections - Nienaber, J. J. C.; Kusne, S.; Riaz, T.; Walker, R. C.; Baddour, L. M.; Wright, A. J.; Park, S. J.; Vikram, H. R.; Keating, M. R.; Arabia, F. A.; Lahr, B. D.; Sohail, M. R.; et al. (Clinical Infectious Diseases, 2013)